PSYCHOSOMATIC FEATURES AND THE LEVEL OF DEPRESSION WITH CHRONIC HEART FAILURE IN PATIENTS WITH ARTERIAL HYPERTENSION AND CORONARY HEART DISEASE - Khusainova Munira Alisherovna; Yarmatov Suvon Totlibayevich; Gafforov Xudoyor Xudoyberdiyevich; Kamolova Diyora Jamshedovna (Journals Park Publishing, 2022)
The relevance of the mutual influence of mental and somatic components, the role of psychological factors in the development, clinical course and prognosis of cardiovascular diseases is beyond doubt. According to recent studies, depression is one of the most important factors determining the development and prognosis of cardiovascular diseases. In this regard, special attention is paid to the study of the relationship of depression with arterial hypertension and coronary heart disease.
Keywords: depression, personal anxiety, reactive anxiety, quality of life, integral indicator of quality of life